Pengendalian Kualitas Produk Pada Produksi Cable Protector Dengan Metode Six Sigma - Irwati, Dwi; Anifanindi, Prismawinda; Supriyanto, Supriyanto (JURNAL TEKNIK INDUSTRI, 2023)
Quality anomalies in the production process cause an increase and decrease in the defect ratio during the current period. During the October-December 2021 period, the production of Berhinge cable protectors resulted in a defect ratio of 3,565 ppm. Defects on cracked hinges are the highest contributor to defect data from the entire production of cable protectors. The hinge cracks on the part are caused by parameter deviation which causes the addition of material so that the part loses flexibility. Six sigma is one of a methodologies for determining the source of problems to produce corrective solutions that can prevent recurring problems. This study used the six sigma method in repairing hinge crack anomaly defects in the production of cable protector berhinge. In the implementation of repair activities using six sigma can show a decrease in the ratio of defects in the production process of cable protector berhinge. In the January-March 2022 period there was a decrease in the initial defects ratio of 3,565 ppm which could decrease to 1,905 ppm.